Adolescent Dietary Intakes Predict Cardiometabolic Risk Clustering - Moore, Lynn L. (Eur J Nutr, 2015)
PURPOSE: To prospectively examine the relation between adolescent dietary intake and cardiometabolic risk (CMR) clustering at the end of adolescence. METHODS: Data from the NHLBI Growth and Health Study on 1369 girls enrolled at ages 9–10 in 1987–1988 and followed for 10 years were used to estimate the relative risk of having multiple (≥ 2 or ≥ 3) risk factors in late adolescence associated with usual food intake patterns from 9–17 years of age. Mean food intakes were derived from multiple 3-day diet records and CMR factors included larger waist circumference, insulin resistance, low high-density lipoprotein-cholesterol, high low-density lipoprotein-cholesterol, high triglycerides, and elevated systolic or diastolic blood pressures. RESULTS: Of 1,369 subjects, 18.4% girls had 3–6 prevalent risk factors by the end of adolescence and 35.0% had at least two. Higher intakes of fruit and non-starchy vegetables, dairy, and grains were independently associated with having fewer risk factors as were eating patterns characterized by higher combined intakes of these food groups. After adjusting for age, race, socio-economic status, height, physical activity, and television watching, girls with high intakes of dairy and fruits and non-starchy vegetables (vs. those with lower intakes of both) were nearly 50% less likely to have three or more CMR factors in late adolescence; girls with higher intakes of grains plus fruits and non-starchy vegetables were nearly 60% less likely. CONCLUSION: These results suggest that healthy food consumption patterns during adolescence may prevent accumulation of cardiometabolic risk.